2020
DOI: 10.1177/0969733020907952
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experience of providing ethical care following an earthquake: A phenomenological study

Abstract: Background Ethical care provided by nurses to earthquake victims is one of the main subjects in nursing profession. Objectives Given the information gap in this field, the present study is an attempt to explore the nurses’ experience of ethical care provided to victims of an earthquake. Research design and method A hermeneutic phenomenological study was performed. The participants were 16 nurses involved in providing care to the injured in Kermanshah earthquake, Iran. They were selected using purposeful sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…Some nurses mentioned that they had an intact work conscience and did not fail the patients despite all the deficiencies and problems. The same results were reported by K. Moradi et al ( 2020 ), who showed that nurses are committed to moral care even in times of crisis. These positive experiences gave nurses a better understanding of life and its values, as they turned some negative challenges into positive and constructive ones that can help develop humanistic behaviours.…”
Section: Discussionsupporting
confidence: 86%
“…Some nurses mentioned that they had an intact work conscience and did not fail the patients despite all the deficiencies and problems. The same results were reported by K. Moradi et al ( 2020 ), who showed that nurses are committed to moral care even in times of crisis. These positive experiences gave nurses a better understanding of life and its values, as they turned some negative challenges into positive and constructive ones that can help develop humanistic behaviours.…”
Section: Discussionsupporting
confidence: 86%
“…The lack of human resources requires an increase in workload to provide adequate care for the survivors, which adds additional stress. 21 However, nurses have an ethical obligation not only to care for the patient, but also to care for themselves. Therefore, providing holistic care requires nurses to find a balance between meeting the needs of the patient as well as their own.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In this event, there were 620 deaths, 8,000 wounded, 70,000 homeless, 4,700,000 affected by it, and ≥12,000 damaged buildings. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%